Defining requirements for an Augmented Reality system to overcome the challenges of creating and using design representations in co-design sessions. Issue 2 (2nd April 2020) - O'Hare, Jamie; Dekoninck, Elies; Mombeshora, Mendy; Martens, Philippe; Becattini, Niccolò; Boujut, Jean-Francois
ABSTRACT: Within co-design sessions involving designers and non-designers, the type and characteristics of the design representations employed is known to impact the performance of such sessions in terms of idea generation, idea evaluation and communication. This study captures the challenges practitioners face in creating and using design representations for co-design sessions and goes on to investigate the potential of Spatial Augmented Reality (SAR) to overcome those challenges. The advantages of SAR in this application are that, multiple concepts can be represented using one physical model, concepts can be modified live during the session, and additional equipment (such as head mounted displays or handheld devices) is not required, thus eliminating any possible interference with the natural interactions between participants. Interviews with design practitioners and trials with a prototype SAR system are used to identify the key challenges faced by practitioners in their current use of design representations, and to capture the technology requirements for a SAR system for use in co-design sessions. These findings can inform the work of technology developers and researchers working on systems to support co-design sessions.